Preventing prejudice a guide for counselors, educators, and parents - Ponterotto, Joseph G.; Utsey, Shawn O.; Pedersen, Paul, 1936-; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2006)
The second edition of 'Preventing Prejudice' has been completely revised and expanded to provide the most up-to-date and extensive coverage of prejudice and racism currently available.
Includes bibliographical references and indexes.
Specialized.
Description based on print version record.
Keywords: Prejudices -- United States; Prejudices in children -- United States; Cross-cultural counseling -- United States; Electronic books